Village SDG's: Community Empowerment in Catfish Processing Innovation in Tambaksari - Radisha, Raflian Alviki; Isnaini, Yulia; Pangestuti, Anggi Febriana; Fatmawati, Dian Aulia; Fallah, Muhammad Rizqa Aulia (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This research examines the empowerment of the Tambaksari village community through innovative catfish snack processing, focusing on improving skills and knowledge, increasing catfish market value, and enhancing the village's economy and welfare in accordance with SDGs. Method: Using Action Research (PAR) includes socialization, counseling, training, workshops, mentoring, monitoring, providing access to technology and capital, collaboration with local stakeholders, digital promotion, and marketing. Practical Application: This program is expected to have a long-term impact on the quality of life of the community and raise awareness about the importance of SDGs in sustainable development. Conclusion: The innovation in catfish processing in Tambaksari Village has positively impacted community empowerment and local economic development, showcasing how active participation in local resource-based small businesses creates new opportunities. Increased awareness of catfish's quality and nutritional value also enhances community health and well-being, aligning the program's success with SDGs.